1989
DOI: 10.1159/000293650
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Isoamylase Activity in Uneventful Pregnancies

Abstract: A kinetic test (Phadebas®) was used to determine the isoamylase activity in 50 serum specimens and 159 samples of amniotic fluid. A highly significant difference between the isoamylase patterns of serum and amniotic fluid was ascertained which strongly supports the view that amylase activity in amniotic fluid is not of maternal origin. During the whole course of gestation the activity of pancreatic isoamylase was constantly low whereas there was an increase of nonpancreatic activity (S-type amylase) from 44 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…Both our findings [2] and those reported by various other work groups [6][7][8] support the assumption that the amylase activity measured in the amniotic fluid does not stem from the mother and is not influenced by her amy lase level, it being unable to pass through the placenta due to its high molecular weight. Furthermore it has been demonstrated that only a negligible proportion of the measured activity is of pancreatic origin (5.84 ± 4.04% according to our own investigations), the largest proportion being of nonpancreatic origin (s-type amy lase) [2,6,9,10].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Both our findings [2] and those reported by various other work groups [6][7][8] support the assumption that the amylase activity measured in the amniotic fluid does not stem from the mother and is not influenced by her amy lase level, it being unable to pass through the placenta due to its high molecular weight. Furthermore it has been demonstrated that only a negligible proportion of the measured activity is of pancreatic origin (5.84 ± 4.04% according to our own investigations), the largest proportion being of nonpancreatic origin (s-type amy lase) [2,6,9,10].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore it has been demonstrated that only a negligible proportion of the measured activity is of pancreatic origin (5.84 ± 4.04% according to our own investigations), the largest proportion being of nonpancreatic origin (s-type amy lase) [2,6,9,10]. After evaluating various cytograms, Wolf and Taussig [6] suggest that the ascertained non pancreatic amylase activity does not stem from intes tines or liver, but rather from the fetal salivary gland.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations